Trophic niche variation throughout the year in the opportunistic Kelp Gull at different trophic scenarios in Patagonia, Argentina - Lisnizer, Nora (2021)
Changes in foraging strategies throughout the year are key determinants of seabird population dynamics. However, due to seabird post-breeding dispersal, year-round trophic ecology studies rarely focus on individuals from known colonies. Using stable isotope analysis (δ15N, δ13C) of blood and primary feathers, we tested during 2012 the trophic niche variation throughout the year in Kelp Gulls Larus dominicanus from three colonies in Patagonia, Argentina, located in areas with different availability of anthropogenic food subsidies. Isotopic niche width, measured using multivariate ellipse-based metrics, was wider at all colonies during the non-breeding season, suggesting that during this period gulls forage on a greater variety of food sources possibly related to post-breeding dispersal, seasonal changes in food resources, and/or the relaxation of central place foraging. Individuals from the colony with yearround availability of fisheries discards (Isla Vernaci) presented the lower isotopic niche width year-round compared to those from the other two colonies, one with discards only available during the breeding season (Punta Tombo) and the other with only open-air refuse dumps available all year-round (Punta León). At Isla Vernaci, an abrupt expansion in niche width occurred later in the non-breeding season, after the start of a fisheries moratorium, suggesting that Kelp Gulls remained in nearby areas and partly associated to trawl fisheries between breeding events. Preliminary diet results indicate that most studied individuals from Isla Vernaci were feeding on demersal prey, only available from fisheries discards as Kelp Gulls are surface feeders. These results suggest that the availability of discards can greatly influence Kelp Gull foraging strategies and non-breeding movements, and that changes in niche metrics can be context dependent. Future studies should complement the assessment of niche variability with studies of diet composition throughout the year.